Achieving a Stable, Adequate, and Sustainable Financing of Primary Education in Nigeria - Matthew, Ige Akindele (Research Developments in Arts and Social Studies Vol. 4, 2022)
It needs not be overemphasized that primary education is the foundation on which the other levels of education rest. It can also be likened to the gate of a building, which controls the entrants into it. Despite the importance of primary education, the funding has been unstable, insufficient, and unsustainable in Nigeria. Primary education has over the years been plagued by a 'push and pull syndrome' between the three levels of government (i.e. federal, state, and local). Its funding has also been insufficient to address its problems, posing a financial strain on the government. The history of primary education funding in Nigeria is examined in this study. Specifically, it highlighted the maneuvering among the federal, state, and local governments; the inadequacy, as well as the non-sustainability of the financing. Joint financing by the federal, state, and local governments, the emergence of an Education Tax for public employees, enhanced private sector participation/contributions, enlisting the help of old students, organizing fundraising activities, engaging in farming production, and ensuring accountability in the management of primary education funds are all recommended to achieve adequate, stable, and sustainable financing of primary education.